Changes in immunosuppressive treatment of chronic graft-versus-host disease: comparison of 2 surveys within allogeneic hematopoietic stem cell transplant centers in Germany, Austria, and Switzerland - Wolff, Daniel; Hilgendorf, Inken; Wagner-Drouet, Eva; Jedlickova, Zuzana; Ayuk, Francis; Zeiser, Robert; Schäfer-Eckart, Kerstin; Gerbitz, Armin; Stadler, Michael; Klein, Stefan; Middeke, Jan Moritz; Lawitschka, Anita; et al. (Biology of blood and marrow transplantation, 2019)
Chronic graft-versus-host disease (cGVHD) remains the leading cause of late morbidity and mortality. Despite the growing number of treatment options in cGVHD, evidence remains sparse. The German-Austrian-Swiss GVHD Consortium performed a survey on clinical practice in treatment of cGVHD among transplant centers in Germany, Austria, and Switzerland in 2009 and 2018 and compared the results. The survey performed in 2009 contained 20 questions on first-line treatment and related issues and 4 questions on second-line scenarios followed by a survey on all systemic and topic treatment options known and applied, with 31 of 36 transplant centers (86%) responding. The survey in 2018 repeated 7 questions on first-line treatment and 3 questions on second-line scenarios followed by an updated survey on all current systemic treatment options known and applied, with 29 of 66 centers (43%) responding. In summary, the results show a large overlap of first-line treatment practice between centers and the 2 surveys because of a lack of new data that changes practice, except significant heterogeneity of treatment of cGVHD progressive onset type, which can be explained by the lack of trials focusing on this high-risk entity. In contrast, treatment options applied to second-line therapy vary considerably, with new agents like ibrutinib and ruxolitinib entering clinical practice. Moreover, treatment of bronchiolitis obliterans syndrome demonstrates heterogeneity in applied therapeutic options and sequence because of a lack of controlled data and different conclusions from already existing evidence. In summary, the survey results demonstrate an increasing number of treatment options applied to cGVHD accompanied by a significant heterogeneity in second-line treatment and underline the urgent need for clinical trials and registry analyses on rare entities with high mortality like progressive onset type and lung involvement of cGVHD.
Gesehen am 06.12.2019